2011
DOI: 10.22456/2316-2171.14348
|View full text |Cite
|
Sign up to set email alerts
|

Musicoterapia E Exercícios Terapêuticos Na Qualidade De Vida De Idosos Institucionalizados

Abstract: RESUMOIntrodução: O Brasil assume hoje, um perfil demográfico diferente daquele que atribuía à sua população a característica de um país de jovens. Com a senescência, ocorre diminuição da capacidade de órgãos e sistemas em executar funções, resultando em maior vulnerabilidade e perdas funcionais progressivas, aumentando a dependência do idoso. A musicoterapia e os exercícios terapêuticos vêm colaborar para melhor qualidade de vida do idoso institucionalizado. Objetivo: Avaliar a qualidade de vida de Idosos Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In institutionalized seniors, it was observed that music therapy contributed positively to their quality of life, allowing them to recover the playful, emotional, spiritual, and sensitive aspects, a practice that promotes dignity of life and humanization 3,4 . In older adults with dementia, music therapy showed improvement in anxiety, apathy, and agitation.…”
Section: Music Applied To Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In institutionalized seniors, it was observed that music therapy contributed positively to their quality of life, allowing them to recover the playful, emotional, spiritual, and sensitive aspects, a practice that promotes dignity of life and humanization 3,4 . In older adults with dementia, music therapy showed improvement in anxiety, apathy, and agitation.…”
Section: Music Applied To Older Adultsmentioning
confidence: 99%
“…It also helps to control psychological and physical symptoms, such as anxiety, depression, and pain, as well as promoting relaxation, pleasure, and the strengthening of interpersonal relationships 2 . Music therapy favors the construction of humanized environments in health care 3 . The results of research investigating the influence of music on pain are controversial.…”
Section: Introductionmentioning
confidence: 99%